2007
DOI: 10.1007/s10722-007-9285-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Jatropha species as revealed by RAPD markers

Abstract: The genus Jatropha is native of tropical America with more than 200 species that are widely distributed in tropics with a promise for use as an oil crop for biodiesel. This investigation was carried out to assess the genetic diversity of 12 Jatropha species based on random amplified polymorphic DNA markers. From 26 random primers used, 18 primers gave reproducible amplification banding patterns of 112 polymorphic bands out of 134 bands scored accounting for 80.2% polymorphism across the genotypes. Three primer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 24 publications
4
45
0
2
Order By: Relevance
“…In the present study, the highest rate of genetic similarity was found within J. curcas and then between J. curcas and J. integerrima, which is in agreement with Ganesh et al (2008) and Tanya et al (2011b). EST-SSR primers identified in this study had a good cross species/genera amplification efficiency and thus are useful to identify genetic diversity of J. curcas and its close taxa as well as to choose the desired related species for wide crossing to improve jatropha.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the highest rate of genetic similarity was found within J. curcas and then between J. curcas and J. integerrima, which is in agreement with Ganesh et al (2008) and Tanya et al (2011b). EST-SSR primers identified in this study had a good cross species/genera amplification efficiency and thus are useful to identify genetic diversity of J. curcas and its close taxa as well as to choose the desired related species for wide crossing to improve jatropha.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic relatedness among the Jatropha species/genera Many studies were carried out to analyze the genetic relatedness among Jatropha species with markers, such as amplified fragment length polymorphism (Pamidimarri et al 2009), ISSR (Tanya et al 2011b), randomly amplified polymorphic DNA (Ganesh et al 2008;Pamidimarri et al 2009) and SSR (Pamidimarri et al 2011;Tanya et al 2011a). In the present study, the highest rate of genetic similarity was found within J. curcas and then between J. curcas and J. integerrima, which is in agreement with Ganesh et al (2008) and Tanya et al (2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Dendrogram obtained by the UPGMA method (Figure 2) revealed two major groups at Jatropha germplasm: one made up of wild accession and another group with accessions of J. curcas from Brazil, Mexico, China, and the improved Backcross genotypes. Similar results were reported by Ganesh-Ram et al (2008). Our dendrogram revealed that Mexican genotypes were not grouped in a separately and single cluster.…”
Section: Discussionsupporting
confidence: 90%
“…Molecular markers like RAPD (randomly amplified polymorphic DNA), AFLP (amplified fragment length polymorphism), SSR microsatellites (simple sequence repeat), ISSR (inter-simple sequence repeat), among others have been employed to assess genetic diversity in J. curcas germplasm from different parts of the world (Basha and Sujatha, 2007;Ganesh-Ram et al, 2008;Grativol et al, 2011;Tanya et al, 2011;Sudheer et al, 2011;PecinaQuintero et al, 2014). Most of these studies have reported narrow diversity in germplasm (Basha and Sujatha, 2007;Sun et al, 2008;Shen et al, 2010), independent from the marker system used, which indicate the need to broaden the genetic base in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Highest genetic similarity and minimum polymorphism was found in Jatropha curcas by RAPD analysis. Basha and Sujatha (2007) and Ram et al (2007). In this work, we compared the applicability of ISSRs and RAPDs as genetic markers to characterize the four Jatropha species genotypes.…”
Section: Discussionmentioning
confidence: 99%